Oenococcus oeni Exopolysaccharide Biosynthesis, a Tool to Improve Malolactic Starter Performance - Dimopoulou, Maria; Raffenne, Jerôme; Claisse, Olivier; Miot-Sertier, Cécile; Iturmendi, Nerea; Moine, Virginie; Coulon, Joana; Dols-Lafargue, Marguerite (Frontiers in Microbiology, 2018)
Oenococcus oeni is the lactic acid bacterium that most commonly drives malolactic fermentation in wine. Though the importance of malolactic fermentation in terms of wine microbial stability and sensory improvement is well established, it remains a winemaking step not so easy to control. O. oeni displays many adaptation tools to resist the harsh wine conditions which explain its natural dominance at this stage of winemaking. Previous findings showed that capsular polysaccharides and endogenous produced dextran increased the survival rate and the conservation time of malolactic starters. In this paper, we showed that exopolysaccharides specific production rates were increased in the presence of single stressors relevant to wine (pH, ethanol). The transcription of the associated genes was investigated in distinct O. oeni strains. The conditions in which eps genes and EPS synthesis were most stimulated were then evaluated for the production of freeze dried malolactic starters, for acclimation procedures and for malolactic fermentation efficiency. Sensory analysis tests on the resulting wines were finally performed.